The Relationship between Frequency of Consumption of Cariogenic Foods and DMF-T Index in 12-Year-Old Children - Yenti, Aflinda; Damhuji, Damhuji; Safitri, Handreni Yulian (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The most common oral disease in Indonesia is dental cavities, especially common in school-age children due to their tendency to favor sweet and sticky foods that can cause dental caries. This study aims to identify the relationship between the frequency of cariogenic food consumption and the DMF-T index in 12-year-old children at SDN 05 Batu Taba, Ampek Angkek District, Agam Regency in 2023. This type of research is an analytic study with a cross-sectional design. The study population included 47 respondents aged 12 years from SDN 05 Batu Taba. The research methods involved interviews regarding the frequency of cariogenic food consumption and DMF-T index examination. Data analysis involved univariate and bivariate analysis, with the chi-square test used for bivariate analysis. The results showed that the frequency distribution of cariogenic food consumption was categorized as low 63.8%, medium 19.1%, high 17.0%, and very high 0%. The frequency distribution of dental caries in the good category reached 42.6%, while the bad category reached 57.4%. The statistical test results showed a ρ value of 0.016 <0.005. The conclusion of this study is that there is a significant relationship between the frequency of cariogenic food consumption and the DMF-T index in 12-year-old children at SDN 05 Batu Taba, Ampek Angkek District, Agam Regency. It is recommended to intensify the longitudinal study to better understand the behavioral changes of cariogenic food consumption frequency and its impact on DMF-T index over time.